Agroecological Characteristic and Potency of Arrowroot on Several Elevation in Garut District, West Java - Asep Rohandi, S.Hut., M.Si. (Jurnal Agroforestri Indonesia, 2021)
ABSTRACTArrowroot (Maranta arundinacea L.) is a multipurpose plant that can grow under the stands so that the species has the potential to develop in the pattern of agroforestry. Initial information of arrowroot plant population as a source of germplasm for plant material/superior varieties and their agroecological characteristics in the field is indispensable. The study aims to determine the distribution, agroecological characteristics and potency of arrowroot in Garut regency. The methods include: (1) the study of literature and direct communication with stakeholders and the public, (2) field survey to collect data on distribution, cultivation status, abundance and productivity of arrowroot plant using a single plot, and (3) data collection of arrowroot agroecological characteristics include: vegetation analysis and geoklimat factors. The research results indicate that the arrowroot populations distribute in groups with a fairly broad ecological range i.e. altitude 6-1351 masl, temperature 20-36oC, relative humidity RH 40-72%, light intensity 12-56% dan pH 4.16-7,40 (acid to neutral) and in the low to high soil fertility condition. Falcataria moluccana as the major private forest species dominates in all zones of altitude, especially on the stage of the tree. Arrowroot abundance by elevation zones is 63,750 plants/ha (lowlands), 43,864 plants/ha (plains) and 73.333 plants/ha (plateau). The potential production for all elevations ranged from 15.40 to 163.2 g/plants. Cikajang and Cilawu populations have good potential to produce the high yield of tuber for arrowroot cultivation in Garut District.